MENGEMBANGKAN KOMPETENSI PEDAGOGIK GURU PAI SD/MI DENGAN MODEL PEMBELAJARAN KOOPERATIF - Rofiah, Nurul Hidayati (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
Teacher’s pedagogical competence can be developed and the quality can be increased through the application of cooperative learning model. By using this model, a teacher could use many interesting methods to improve the students’ interest, motivation and achievement. By this strategy, the learning interaction will be more “many-direction” and learning source diversification. The cooperative learning strategy was directed to develop the students’ cognitive ability as well as their interpersonal competence. Cooperative learning strategy is one of the alternatives can be used in Islamic Education for effective and efficient learning to achieve the determined learning goals. Cooperative learning strategy is psychologically suitable with the students’ social development in their age of SD/MI and suitable with their characteristic that is to enjoy working in groups. Cooperative learning strategy is also a reflection of the Indonesian character namely mutual cooperation. Therefore, the learning should be suitable with the society condition and the mutual cooperation should be the principle coloring this learning practice for the students. In the application of cooperative learning, it needs the willingness and the ability as well as the teachers’ creativity to manage class, so the teacher will be more active especially in making well-done lesson plans, class management in action, and make assignment for students with groups.